Heme biomolecule as redox mediator and oxygen shuttle for efficient charging of lithium-oxygen batteries - Won-Hee Ryu (Nature Portfolio, 2016)
Natural biomolecules including heme-like porphyrins can be applied as sustainable chemical catalysts in lithium-oxygen batteries. Here, the authors show that the heme molecule can function as a soluble redox catalyst and oxygen shuttle for efficient oxygen evolution in non-aqueous lithium-oxygen cells.